Outcomes of university Spanish heritage language instruction in the United States - Bowles, Melissa A.; Torres, Julio; Beaudrie, Sara M.; Holmes, Bonnie C.; Bello-Uriarte, Adrian; Zamora, Celia Chomón; Cuenca, Sara Fernández; Vergara Wilson, Damián; Holguín Mendoza, Claudia; Pascual y Cabo, Diego (Georgetown studies in Spanish linguistics., 2022)
Outcomes of University Spanish Heritage Language Instruction in the United States addresses for the first time how receiving heritage classroom instruction affects Spanish speakers on multiple levels, including linguistic, affective, attitudinal, social, and academic outcomes.